SYNTHETIC AMPHOTERIC CRYOGELS AS AN ANTIDOTE AGAINST ACUTE HEAVY METAL POISONING - Baimenov, Alzhan; Fakhradiyev, Ildar; Berillo, Dmitriy; Saliev, Timur; Mikhalovsky, Sergey; Nurgozhin, Talgat; Inglezakis, Vassilis J. (MDPI, 2021)
The effectiveness of an amphoteric cryogel (AAC) as an oral sorbent (enerosorbent) for the treatment of acute poisoning of small animals (rats) with heavy metals (HMs) was studied in in vivo experiments. The morphological structure of the cryogel was examined using scanning electron microscopy/energy-dispersive X-ray analysis and confocal microscopy. The use of the cryogel in the treatment of rats administered an LD50 dose of Cd(NO3)2, CsNO3, Sr(NO3)2, or HgCl2 in aqueous solution showed their high survival rate compared to the control group, which did not receive such treatment. The histological and chemical analysis of internal tissues and the biochemical analysis of the blood of the experimental animals showed the effectiveness of the cryogel in protecting the animals against the damaging effect of HMs on the organism comparable with unithiol, a chelating agent based on 2,3-dimercapto-1-propane sulfonic acid sodium salt (DMPS) approved for the treatment of acute poisoning with some heavy metals. Keywords: cryogel; antidote; DMPS; elimination; heavy metals
Keywords: Type of access: Open Access; cryogel; antidote; DMPS; elimination; heavy metals